KONTRIBUSI SUB SEKTOR PERHOTELAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN PINRANG TAHUN 2013-2017 - T, Ruslang; Bahruddin, Bahruddin; Mica, Mica (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2021)
Tourism development programmed by both the government and the private sector will be directed at efforts to increase the number of tourist visits because it is a significant source of income. This study aims to determine the contribution of the hospitality sub-sector to the Gross Regional Domestic Product of Pinrang Regency in 2013-2017. Data collection techniques used in this study are interviews, observation, documentation. The sample in this study was 19 (nineteen) hotels in Pinrang Regency. The data analysis technique in this study used a quantitative descriptive method. With the results of the research, namely the Hospitality Sub-Sector in Pinrang Regency, providing a positive value in supporting the Gross Regional Domestic Product of Pinrang Regency, with the results in 2013 the Hospitality Sub-Sector contributed 0.87% in 2014 Revenue the Hospitality Sub-Sector Contribution increased by 0.89% In 2015 Revenue contribution from the Hospitality Sector decreased by 0.86% in 2016 Revenue from the Hospitality Sector increased by 0.88% and in 2017 Syb Revenue contribution from the Hospitality Sector increased by 0.89%.